INTEGRASI PASAR BERAS INDONESIA DENGAN PASAR BERAS INTERNASIONAL - Catur Sugiyanto; Soetatwo Hadiwigeno (JURNAL EKONOMI DAN KEBIJAKAN PEMBANGUNAN, 2012)
The food crisis that was triggered by climate change has swept the world lately. Climate change is affecting the pattern of the world that led to changes in the pattern of agricultural production as well. Changes in the pattern of production results in world food production schedule was delayed, and along with these changes, many countries export so that world food prices increase. Rising world food prices starting from US and then spread in the other parts of the world, including Indonesia. However, it is unknown how big relatedness of International food prices changes with food prices in Indonesia. This paper aims to analyze the connectedness between domestic rice market with international market, how long shock in international rice impact on the domestic market and to analyze interlinkage in domestic primary rice market.  Using data rice price in indonesia and international rice price of FAO, writer found that market rice integrated both in domestic and foreign, so the fluctuations in both markets would affect each other Keywords:  Food Crisis, Production Pattern,  Domestic and International Market Integration